Persicoimidate Isolated from Allium ampeloprasum Subsp. Persicum with Apoptotic Effects against Breast Cancer Cell Lines: Apoptotic effects of Persicoimidate - Naji Esfahani, Seyed Saeed; Sadeghi Dinani, Masoud; Moazen, Fatemeh; Shafiee, Fatemeh (Iranian Journal of Pharmaceutical Sciences, 2020)
Breast cancer is the most common malignancy among American women and the second leading cause of cancer death after the lung cancer. For this reason, trying to find new drugs for the treatment of this disease is essential. The aim of the present study was to evaluate the cytotoxic effects of three cinnamic acid derivatives isolated from Allium ampeloprasum var. Persicum including Caffeoyl tyramine, Feruloyl tyramine, and Persicoimidate on two breast cancer cell lines, MCF-7 and BT-474. Evaluation the cytotoxic effects of mentioned purified compounds against MCF-7 and BT-474 cells was performed using MTT assay and their IC50 was determined. Finally, flow cytometery analysis on MCF-7 cells was performed and used to determine the cell death mechanism of investigated compounds. The results exhibited that the cytotoxic effects of all three compounds against breast cancer cell lines was concentration-dependent. The IC50 of Caffeoyl tyramine, Feruloyl tyramine, and Persicoimidate was determined to be as 73, 56, and 40 μg/ml for MCF-7 and 100, 54, and 37 μg/ml for BT-474 cells, respectively. So, Perscicoimidate showed the most potent cytotoxic effects against two breast cancer cells. Finally, flow cytometery analysis showed that Persicoimidate caused approximately 48% of apoptosis in concentration of 40 μg/ml. According to the tyrosine kinase inhibitory activity of cinnamic acid derivatives, these compounds has the potential of being cancer drug candidates for complementary studies on breast tumors with highly expression of EGF receptor. However, evaluation of anticancer effects of these compounds against other breast cancer cell lines is suggested.